2013
DOI: 10.5455/medscience.2013.02.8052
|View full text |Cite
|
Sign up to set email alerts
|

Should FISH Test be Performed to all Patients With Breast Cancer?

Abstract: CerbB2 receptor determination is very important for the prognosis and treatment of breast cancer. The most used two methods for CerbB2 receptor determination are immunohistochemistry and FISH methods. FISH method is recommended for immunohistochemically CerbB2 (++) patient group. Therefore, even though the immunohistochemically CerbB2 (++) patients are in the same group, FISH test divides the results into two separate groups. Our study compared these two groups in terms of relaps duration. Total of 85 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Osteoarthritis is a degenerative disease with clinical manifestations, including joint pain, tenderness, stiffness, joint swelling, restricted movement and joint deformities (1). In recent years, the incidence of osteoarthritis has increased and presents as a serious threat to human health and quality of life (2)(3)(4). The causes of osteoarthritis are complex, therefore it is difficult to develop a comprehensive classification system and its pathogenesis remains unclear (5).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis is a degenerative disease with clinical manifestations, including joint pain, tenderness, stiffness, joint swelling, restricted movement and joint deformities (1). In recent years, the incidence of osteoarthritis has increased and presents as a serious threat to human health and quality of life (2)(3)(4). The causes of osteoarthritis are complex, therefore it is difficult to develop a comprehensive classification system and its pathogenesis remains unclear (5).…”
Section: Introductionmentioning
confidence: 99%
“…25 Moreover, Her-2 receptor expression was shown to be associated with aggressive characteristics of BC. 26,27 Li et al 27 demonstrated high Her-2 expression in BC patients with ALN metastasis. In a recent retrospective cohort study, Her-2-positive status was associated with a higher risk of ALN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, Her-2 receptor expression was shown to be associated with aggressive characteristics of BC. 26,27 Li et al. 27 demonstrated high Her-2 expression in BC patients with ALN metastasis.…”
Section: Discussionmentioning
confidence: 99%